2018
DOI: 10.3390/molecules23071682
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic Characterization, and In Vitro Antibacterial Evaluation of Novel Functionalized Sulfamidocarbonyloxyphosphonates

Abstract: Several new sulfamidocarbonyloxyphosphonates were prepared in two steps, namely carbamoylation and sulfamoylation, by using chlorosulfonyl isocyanate (CSI), α-hydroxyphosphonates, and various amino derivatives and related (primary or secondary amines, β-amino esters, and oxazolidin-2-ones). All structures were confirmed by 1H, 13C, and 31P NMR spectroscopy, IR spectroscopy, and mass spectroscopy, as well as elemental analysis. Eight compounds were evaluated for their in vitro antibacterial activity against fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…[29] Bouzina and al. [30] evaluated the antibacterial activity of a new series of sulfamidocarbonyloxyphosphonates and demonstrated that all tested compounds had an important inhibition against Gram negative strains than Gram positive. This finding supports our findings, showing that sulfonamide chemicals are more efficient against Gram negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Bouzina and al. [30] evaluated the antibacterial activity of a new series of sulfamidocarbonyloxyphosphonates and demonstrated that all tested compounds had an important inhibition against Gram negative strains than Gram positive. This finding supports our findings, showing that sulfonamide chemicals are more efficient against Gram negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, a series of seven N,N-bis (2-chloroethyl) sulfamido carbonyloxymethylphosphonate derivatives (1 b-7 b) and their cyclic analogs (1 c-7 c) were synthesized by a carbamoylationsulfamoylation reaction of seven α-hydroxyphosphonates, followed by intramolecular cyclization. The impact of the aromatic substituent in the alpha position of the phosphonate Compound 5 [25] Treatment…”
Section: Discussionmentioning
confidence: 99%
“…Because sulfonamide and sulfamide compounds have been widely studied for their antimicrobial activities some sulfonamidocarbonyloxymethylphosphonates were also recently developed in our laboratory, as potential antimicrobial agents against Gram-positive and negative bacteria and have shown significant antibacterial activity [25] compared to sulfamethoxazole/trimethoprim as a reference (Figure 1, compound 5).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the introduction of cyclosulfamide and Nsulfamoyloxazolidin-2-one into glucosamine structure can lead to interesting new chemical and pharmacological potentialities due to their biological activities with a broad application as synthetic intermediates (Bouzina et al, 2021;Nicolaou et al, 2004) especially in the asymmetric synthesis (F ecourt et al, 2010). They present a variety of interesting and useful properties that make them attractive as cyclic scaffolds for peptidomimetics in the design of protease inhibitors such as HIV protease (Hult en et al, 1999;Jadhav & Woerner, 1995;Schaal et al, 2001), serine protease (Groutas et al, 2001;He et al, 2000;Kuang et al, 2000;Yang et al, 2008), metalloprotease (Ducry et al, 1999), inhibitors of noroviruses (Dou et al, 2012), glycosidase inhibitors (Benltifa et al, 2008), and antibacterial activity (Abbaz et al, 2014;Bouzina et al, 2018).…”
Section: Introductionmentioning
confidence: 99%